Non-random genomic integration - an intrinsic property of retrogenes in Drosophila? - Metta Muralidhar; Schlötterer Christian (BMC Evolutionary Biology, 2010)
Abstract Background The Drosophila X-chromosome shows a significant underrepresentation of genes with male-biased gene expression (demasculinization). This trend is matched by retrogenes, which typically have a male biased gene expression pattern and show a significant movement bias from X-chromosomes to autosomes. It is currently assumed that these patterns are best explained by selection, either mediated by male meiotic sex chromosome inactivation (MSCI) or sexually antagonistic forces. We scrutinized the evolutionary dynamics of retroposition by focusing on retrogenes for which the parental copy has degenerated. Results Consistent with a functional substitution of the degenerated gene by the retrogene, patterns of sequence evolution and gene expression were similar between retroposed and parental genes. Like previous studies, our set of retrogenes showed a significant movement off the X-chromosome. In contrast to data sets where retroposition caused gene duplication, the genes in our study showed primarily female-biased or unbiased gene expression. Conclusions Based on our results, the biased transposition pattern cannot be explained by MSCI and probably not by sexual antagonism. Rather, we propose that the movement away from the X-chromosome represents a general property of retroposition in Drosophila.